2019
DOI: 10.3389/fcimb.2018.00443
|View full text |Cite
|
Sign up to set email alerts
|

Itaconimides as Novel Quorum Sensing Inhibitors of Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa is known as an opportunistic pathogen that often causes persistent infections associated with high level of antibiotic-resistance and biofilms formation. Chemical interference with bacterial cell-to-cell communication, termed quorum sensing (QS), has been recognized as an attractive approach to control infections and address the drug resistance problems currently observed worldwide. Instead of imposing direct selective pressure on bacterial growth, the right bioactive compounds can prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 58 publications
1
41
0
Order By: Relevance
“…For example, it was reported that treatment with a QS inhibitor and TOB resulted in an increased clearance of P. aeruginosa in a foreign body infection model, demonstrating that this approach can work in vivo [23]. Another study demonstrated eradication of P. aeruginosa biofilms when a QS inhibitor and TOB were combined [51]. Sub-MIC CAD and 2×MIC of TOB had demonstrated a significant inhibition of P. aeruginosa biofilms [22].…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was reported that treatment with a QS inhibitor and TOB resulted in an increased clearance of P. aeruginosa in a foreign body infection model, demonstrating that this approach can work in vivo [23]. Another study demonstrated eradication of P. aeruginosa biofilms when a QS inhibitor and TOB were combined [51]. Sub-MIC CAD and 2×MIC of TOB had demonstrated a significant inhibition of P. aeruginosa biofilms [22].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several natural substances with known biological properties act as QS inhibitors as they intervene in QS-associated pathways, attenuate QS gene expression, and impair the infection. Recently, several reports claim to quench QS or ameliorate the QS signals through various synthetic molecules, natural products, and enzymes (Fong et al, 2018). For instance, acyl homoserine lactone analogs such as N-acyl cyclopentyl amines (Cn-CPAs), lactonase SsoPox, N-acylhomoserine lactonase, and AiiM (Guendouze et al, 2017;López-Jácome et al, 2019) were effective as QSIs against P. aeruginosa.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] Literature is full of reports particularly on quorum sensing inhibition in Pseudomonas aeruginosa. [25][26][27][28][29][30][31][32][33][34][35][36] Carvacrol (essential oil) was reported to inhibit biolm formation in S. aureus and P. aeruginosa and pyocyanin production in P. aeruginosa signicantly. 37 Baicalein (avonoid from the roots of Scutellaria baicalensis) was demonstrated to inhibit several virulence factors and biolm formation.…”
Section: Introductionmentioning
confidence: 99%